Defining the Government's Debt and Deficit - Irwin, Timothy (IMF Working Papers; Working Paper ;, 2016)
Although the budget deficit and the public debt feature prominently in political debate and economic research, there is no agreement about how they should be measured. They can be defined for different sets of public institutions, including the nested sets corresponding to central government, general government, and the public sector, and, for any definition of government, there are many measures of the debt and deficit, including those generated by four kinds of accounts (cash, financial, full accrual, and comprehensive), which can be derived from four nested sets of assets and liabilities. Each debt and deficit measure says something about public finances, but none tells the whole story. Each is also vulnerable to manipulation, and is likely to be manipulated if it is subject to a binding fiscal rule or target. Narrow definitions of government encourage the shifting of spending to entities outside the defined perimeter of government. Narrow definitions of debt and deficit encourage operations involving off-balance-sheets assets and liabilities, while broad measures are susceptible to the mismeasurement of on-balance-sheet assets and liabilities. Reviewing the literature on these issues, the paper concludes that governments should publish several measures of the debt and deficit in a form that clearly reveals their interrelationships.